2000
DOI: 10.1128/aac.44.2.456-457.2000
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Mercury and Antimicrobial Agents in Streptococcus mutans Isolates from Human Subjects in Relation to Exposure to Dental Amalgam Fillings

Abstract: Resistance to cefuroxime, penicillin, tetracycline, and mercury is reported for 839 Streptococcus mutans isolates from 209 human study subjects. The MICs of these drugs did not differ for isolates from one dental amalgam group and two nonamalgam subsets: a group with no known exposure to amalgam and a group whose members had their amalgam fillings removed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 24 publications
0
23
0
1
Order By: Relevance
“…These patients included those never exposed to amalgam fillings, those with fillings and those whose fillings had been removed. The isolates of S. mutans recovered from these patients were tested for susceptibility to CHX and the antibiotics tetracycline, penicillin and cefuroxime (Leistevuo et al 2000). The results indicated that the susceptibility profiles of these strains to CHX and the antibiotics tetracycline, penicillin and cefuroxime were comparable to their previous results reported in 1993.…”
Section: Clinical Studies Indicate That ‘Real‐life Use’ Of Antiplaquementioning
confidence: 99%
“…These patients included those never exposed to amalgam fillings, those with fillings and those whose fillings had been removed. The isolates of S. mutans recovered from these patients were tested for susceptibility to CHX and the antibiotics tetracycline, penicillin and cefuroxime (Leistevuo et al 2000). The results indicated that the susceptibility profiles of these strains to CHX and the antibiotics tetracycline, penicillin and cefuroxime were comparable to their previous results reported in 1993.…”
Section: Clinical Studies Indicate That ‘Real‐life Use’ Of Antiplaquementioning
confidence: 99%
“…Chlorhexidine is a widely used antibacterial agent, but lack of evidence on long-term clinical outcomes and reported side effects limits its application for caries prevention [Autio-Gold, 2008]. Moreover, S. mutans was reported to develop resistance against other antibacterial agents such as cefuroxime, penicillin and tetracycline used for prophylaxis [Leistevuo et al, 2000]. The potential of appropriate new antimicrobial agents for long-term caries management was highlighted recently [ten Cate, 2009;Filoche et al, 2010].…”
Section: Effect Of Gallium On Growth Ofmentioning
confidence: 99%
“…Leistevuo et al (2000) reported resistance to cefuroxime, penicillin, and tetracycline in 839 strains of S. mutans. In another study, bLactamase-producing strains including Prevotella intermedia, P. denticola, and F. nucleatum were isolated from patients with dental caries (Fosse et al 1999).…”
Section: Resistance To Antimicrobial Agents Among Oral Bacteriamentioning
confidence: 97%
“…Therefore, one of the most urgent and important biomedical challenges of our times is to clarify the role of microbial communities in human health (Belda-Ferre et al 2011;Turnbaugh et al 2007;Ximénez-Fyvie et al 2000). Unfortunately, the antibiotic therapies have rendered these bacteria resistant to traditional antibiotics (Leistevuo et al 2000;Sweeney et al 2004). Therefore, it has been envisaged that the metal oxide nanoparticles with antimicrobial activity (nanoantibiotics) could offer a good alternative to abate and/or control the growth of bacteria in oral cavity (Allaker 2010).…”
Section: Introductionmentioning
confidence: 98%